Conservative management of a button battery tracheoesophageal fistula in a resource-limited setting: a case report - Thadei Liganga; Desderius Chussi; Ezekiel Gathii (Journal of Pediatric Surgery Case Reports)
Introduction: Tracheoesophageal fistula (TEF) is a morbid and potentially fatal complication of button battery ingestion. Conservative management is usually the initial management of choice. A minimum of 4–8 weeks is required for a spontaneous closure of the TEF. Case presentation: A 3-year-old male child presented with hypersalivation, throat pain, choking when feeding, and dysphagia after an accidental ingestion of a lithium button battery 8 hours prior to admission. Esophagoscopy revealed a button battery in the proximal esophagus and circumferential necrosis of the esophageal mucosa at the site. We placed a nasogastric (NG) tube for enteral feedings and kept him without any oral feedings for seven days. At that point we removed the NG tube and initiated oral feedings. He quickly developed choking, so we did a contrast esophagram. Contrast spilled into the airway, confirming the diagnosis of a TEF in the proximal esophagus. We replaced the NG tube and kept him exclusively on NG feedings for 5 more weeks. Follow-up contrast esophagrams were done on the 6th, 10th and 16th weeks post injury, which showed a gradual reduction in the fistula size. No further TEF was seen 16 weeks post injury, so we removed the NG tube and restarted oral feedings. A follow-up study 3 months later showed no abnormalities, and he has been asymptomatic since then. Conclusion: Spontaneous closure of button battery-induced TEFs can be expected to take up to 16 weeks. Prolonged conservative management should be considered before shifting to a surgical approach.